Influence of Competency Human Resources , Utilization Information Technology and Applications Accounting Standards Government (SAP) on the Quality of Financial Reports with Control Internal as an Intervening Variable (Empirical Study at BLUD Community Health Center in Musi Banyuasin Regency) - Ardiyanto, Redhy; Rahayu, Sri; Gowon, Muhammad (PT FORMOSA CENDEKIA GLOBAL, 2024)
We investigated the effects of many factors on the quality of financial reports at a health center in Musi Banyuasin Regency, including human skills, technology utilization, and adherence to government accounting laws. Using a tool called SmartPLS 4.0, we applied a technique known as quantitative analysis. The findings demonstrated that, either directly or indirectly through internal control mechanisms, human abilities, technological application, and adherence to accounting regulations can all have an impact on the caliber of financial reports.